Cytologic examination of the thoracocenthesis fluid for the diagnosis of a malignant mesothelioma and adenocarcinoma. A comparative diagnosis. - Ahmad Ghozali, Ahmad Ghozali (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1993)
Reccurent pleural effusions are frequently the first manifestation of a diffuse malignant pleural mesothelioma. Pleural effusion of the malignant mesothelioma is frequently indistinguishable from the pleural effusion due to adenocarcinoma. The prognosis of this tumor is poor, but immediate and accurate therapy will render prolonged remission. For these reasons, microscopic examination of thoracocenthesis fluid is necessary, because it may provide an immediate diagnosis.Unfortunately, the reliability of cytologic diagnosis is still disputable. Based on microscopic examination, there is no single pathognomonic feature. The cytologic diagnosis of a malignant pleural examination is based on the constellation of findings. The history of the course of the disease, optimal sample preparation, and special stains are important requirements to provide definitive diagnosis.Key Words: mesothelioma adenocarcinoma thoracocenthesis fluid air-dried May Grunwald - Giemsa monoclonal antibody B72.3